PEMAHAMAN HADIS RIWAYAT BUKHARI NOMOR INDEKS 5445 TENTANG BUAH KURMA SEBAGAI OBAT HERBAL PERSPEKTIF ILMU KESEHATAN - Nur Annisa Istifarin; Andris Nurita (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
As stated in the Qur'an and Hadith, dates were the prophet's preferred fruit. The numerous, dispersed hadiths about herbal medicine inspired this research. This research specifically mentions palm fruit as a herbal medicine. Dates are believed to have many benefits that give the effect of human survival. This study's goal is to analyze dates in the context of medical science in the Bukhari hadith. This study used a descriptive method with library research studies (literature review) taken from books, journal articles both national and international. The results and discussion of this study are the content and efficacy of dates in health sciences as well as understanding of the hadith of Bukhari history about dates as herbal medicine. This study concluded that in the dates there are useful ingredients such as being able to reduce blood pressure, boost the immune system and others.